Га.Шаравжамцын найруулал дахь домгуудын тухай: Myths in essays by Ga.Sharavjamts - Рүнь, Фү (Mongolian Studies, 2023)
Essays by Ga.Sharavjamts are enriched broadly by myths, tales and dreams. Analyzing his works, it is clear that he has strong feelings and beliefs and tried the readers to be believed in its deep historical and mythical contents.